Time and archaeology - Murray, Tim, 1955- (One world archaeology, 1999)
This survey of time and archaeology includes chapters from a broad, international range of contributors and combines theoretical and empirical material. They illustrate and explore the diversity of archaeological approaches to time. The contributors contrast between a scientific understanding of time and social, cultural and religious ideas of time, and show how both are important to archaeology. While much archaeological research into time has focused on the key issue of attempting to understand how people in the past had different concepts of time, this collection also shows how developing a fundamental understanding of archaeological time is central to all archaeology, and impacts on its theory and practice.